The Legality of Providing Legal Aid to Perpetrators of the Crime of Murder in the Perspective of the Theory of Dignified Justice - Safi’i, Muhlis (The Indonesian Journal of International Clinical Legal Education, 2021)
The Unitary State of the Republic of Indonesia is a state of law. In accordance with Article 1 paragraph (3) of the 1945 Constitution (UUD 1945). As a state of law, Indonesia must guarantee the rights of its citizens to equality and guarantees of justice, including human rights. As stated by Salim, quoting Fredrich Julius Stahl, that the main element of a state based on law is the protection, as well as the recognition of Human Rights (HAM), and upholding dignified justice. Also in Article 28D paragraph (1) of the 1945 Constitution (UUD 1945) reads: "Everyone has the right to recognition, guarantees, protection, and fair legal certainty and equal treatment before the law". This means that the constitution itself has accommodated, the state guarantees the fulfillment of individual rights of citizens and is treated equally before the law. In a state of law, the law is used as the main shield in the movement of government, state, and society. As an effort to realize justice and the spiritual values ​​of humanity (fair and dignified), there is assistance in the form of legal services for every citizen. The existence of a dignified justice theory is a justice provided by a legal system that has spiritual and material dimensions. This theory is a theory of justice that is based on noble values ​​that are rooted in the second principle of Pancasila, "Just and Civilized Humanity" and is inspired by the first principle, "Belief in the One Supreme God".